Improving Teaching and Learning Process Through Language Games - Rezqan Noor Farid; Yansyah Yansyah (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2019)
Teaching and learning process in the classroom tends to be boring. This happened especially in EFL classroom where the students are not fully aware on the material given. Boring class will also happen when teacher brings very difficult or advance material. In fact, this matter will affect the process itself. This problem can be solved through the usage of games in the classroom. Games can be regarded as entertainment during lesson, media to deliver the material, tool for exercise and assignment, and technique to enhance student’s learning. There are four (4) games delivered in this workshop. They are hot potato, big and small number, tic-tac-toe, and chaining the story. These four games are introduced to the instructors of English Transmigration Village in Mandastana, Barito Kuala. The result of this workshop are the instructors enjoyed the activities, they deliberately asking the actual implementation of the games on the classroom, and they have improved their teaching ability.